A study of tidal turbine array - I - Zhang, Xiang (2014)
A wind turbine is a rotating machine that converts kinetic energy into mechanical energy. It is one of the main source of renewable energy that has gained interested in the recent years due to the environmental concerns such as climate change and depletion of fossil fuels. It is also a major source of sustainable energy and can be harvested using both horizontal and vertical axis wind turbines. In order to fully utilize wind energy, research into the technology of wind turbines becomes necessary.